Alice in Wonderland [videorecording (DVD)] - Carroll, Lewis, 1832-1898; Carroll, Lewis, 1832-1898 (Distributed by Buena Vista Home Entertainment and Walt Disney Studios Home Entertainment, 2010)
An animated musical version of Lewis Carroll's tale about a girl named Alice. Alice follows a White Rabbit through a very small door and enters Wonderland, where she has many unusual adventures.